SOCIAL-ECOLOGICAL APPROACH TO THE STUDY OF PLACE NAMES (Scientific journal of the Fergana State University, 2024)
Today it is noticeable that scientific directions that are at the intersection of two or more large fields of science and have interdisciplinary content are rapidly developing. One of the distinctive features of the development of the science of geography today is that its subject area is expanding, and the importance of interdisciplinary research in solving an increasing number of theoretical and practical problems is increasing. This article discusses the main directions of research on geographical names.